2020
DOI: 10.1038/s41598-020-64881-w
|View full text |Cite
|
Sign up to set email alerts
|

Complete sleep and local field potential analysis regarding estrus cycle, pregnancy, postpartum and post-weaning periods and homeostatic sleep regulation in female rats

Abstract: Sleep and local field potential (LFP) characteristics were addressed during the reproductive cycle in female rats using long-term (60–70 days) recordings. Changes in homeostatic sleep regulation was tested by sleep deprivation (SDep). The effect of mother-pup separation on sleep was also investigated during the postpartum (PP) period. First half of the pregnancy and early PP period showed increased wakefulness (W) and higher arousal indicated by elevated beta and gamma activity. Slow wave sleep (SWS) recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 89 publications
2
19
0
Order By: Relevance
“…Pregnancy‐related sleep changes have also been reported in rodents, although the exact nature of the sleep alterations is unclear. Studies have found a reduction in REM and non‐REM (NREM) sleep during the light phase [103,104]. However, two studies showed that pregnancy generally increase NREM and REM sleep [104,105], whereas a third study found decreased sleep [103].…”
Section: Reproductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnancy‐related sleep changes have also been reported in rodents, although the exact nature of the sleep alterations is unclear. Studies have found a reduction in REM and non‐REM (NREM) sleep during the light phase [103,104]. However, two studies showed that pregnancy generally increase NREM and REM sleep [104,105], whereas a third study found decreased sleep [103].…”
Section: Reproductionmentioning
confidence: 99%
“…Studies have found a reduction in REM and non‐REM (NREM) sleep during the light phase [103,104]. However, two studies showed that pregnancy generally increase NREM and REM sleep [104,105], whereas a third study found decreased sleep [103]. The mechanisms underlying these changes are not yet known but may involve hormones [106–108].…”
Section: Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, females exhibit changes in sleep patterns during pregnancy and after the birth of the offspring. Pregnancy-related sleep changes have been observed in humans and rodents 60,61 . Notably, female rats exhibit sleep changes after mating with vasectomized males 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Estrus (EST) cycle was found to affect a variety of physiological functions in female rats including social- and sexual behavior 16 , 17 , anxiety 18 , 19 and sleep 20 . EST cycle is under strict and complex hormonal control with gonadal hormones playing a major role 21 .…”
Section: Introductionmentioning
confidence: 99%